indonesia - Subianto Karoso; Setyo Yanuartuti; Sasanajati, Jajuk; Arif Hidajat (Journal of Practice Learning and Educational Development, 2024)
The aim of this research is to find out and analyze the classroom management of children with special needs through a differentiation approach at SDS Aqil Global Islamic School. This research design uses descriptive quantitative. This research data was collected by distributing questionnaires to educators at SDS Aqil Global Islamic School, then data was obtained from 17 teacher respondents. The results of the research show that Class Management for Children with Special Needs through the differentiation approach has an average score for the Implementation of Class Management for children with special needs in this school, namely obtaining a score in the range of 35.3%, through the differentiation approach it is possible to adapt the learning material to the needs of each child with special needs. Specifically with an average score range of 47.1%. Evaluation and assessment using the differentiation approach fosters self-confidence in children with special needs in the classroom, obtaining a score range of 47.1% and training support for teachers and education staff in implementing a differentiation approach for children with special needs, namely 41.2%. However, a weak aspect of teacher training for classroom management for children with special needs was found with a score range of 35.3%, meaning that from the results obtained, more training was needed for classroom management for children with special needs through a differentiation approach. Based on these results, what stands out is that the differentiation approach can adapt learning materials for children with special needs and evaluation assessments through differentiation can have a big influence on the learning success of children with special needs. Through good classroom management carried out by teachers by implementing a conducive environment, motivating students, varied learning, structural arrangement of learning hours and the work ethic demonstrated by teachers, it is able to increase the effectiveness of learning in the classroom. This research supports the theory of classroom management for children with special needs through a differentiation approach, and supports the implications of this research regarding the importance of classroom management for children with special needs through a differentiation approach and more training for educators and education staff in making teaching and learning activities in the classroom a success.